2021
DOI: 10.1016/j.amsu.2021.102645
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of ilizarov method for management of long tibial bone and soft tissue defect

Abstract: Introduction Patients with open fracture Gustillo-Anderson grade 3 had undergone several surgical procedures, but still ended up with expose long dead bone or infected. Illizarov method was used to address long bone and soft tissue defect after re-debridement with radical resection of long dead bone or infected segment. Methods We included 14 patients (mean age: 30.86 ± 11.49) with non-union tibial fracture with long dead and infected bone segment who had undergone seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The initial search identified 1251 publications. Twenty-three of these met the eligibility criteria for the pooled analysis, including 1153 patients treated by distraction osteogenesis [ 8 , 12 , 14 , 15 , 22 28 , 31 42 ]. Details of each study are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search identified 1251 publications. Twenty-three of these met the eligibility criteria for the pooled analysis, including 1153 patients treated by distraction osteogenesis [ 8 , 12 , 14 , 15 , 22 28 , 31 42 ]. Details of each study are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Details of each study are shown in Table 1 . Extracted data from each study and pooled analysis are shown in by docking site intervention group in Table 2 (planned intervention) [ 12 , 14 , 15 , 23 , 25 28 , 31 33 ] and Table 3 (observed) [ 8 , 24 , 33 , 38 – 42 ]. Where patients from a single study had different docking site protocols, these were included in the relevant group.…”
Section: Resultsmentioning
confidence: 99%
“…Ankle stiffness was observed in 3 patients, with a lower incidence compared to the ilizarov technique. Besides, there was no significant difference in healing time and weight -bearing time of tibial defect treated by ICBG compared with VFG [ 29 ] and ilizarov technology [ 30 ]. Therefore, large ICBG for the treatment of CSBD can be advocated.…”
Section: Discussionmentioning
confidence: 99%
“…They found that radical débridement was the key step in achieving satisfactory bone formation and functional results. Miraj et al 13 reviewed 14 patients with infected tibial nonunions with long devascularized and infected bone segments who had undergone several débridements, bone grafting, or spacer and soft-tissue closure. The patients then underwent radical resection and bone transport.…”
Section: Discussionmentioning
confidence: 99%